FUNDAMENTALS OF THE DESIGN COMPETENCE OF THE FUTURE TEACHER OF TECHNOLOGY - Savchenko Л.О. (Pedagogy of Higher and Secondary Education, 2022)
In article questions of design competence of the teacher of technology are considered. Become concept “competence” and “professionalism” is shown. Design competence includes: ability to integrate earl received knowledge and skills; to take into account intersubject connections; to be able to connect the thed with practice; to focus the student on scientific outlook, creative thinking, development of compotents of professional competence.